Nanocellulose and Its Interface: On the Road to the Design of Emerging Materials. Issue 4 (29th December 2021) - Bettotti, Paolo; Scarpa, Marina
Abstract: Nanocellulose has several unique properties that render it a versatile material with possible uses in a broad spectrum of applications. Nanocellulose is proved to form stable colloidal suspensions with interesting rheological properties, assemble in soft hydrogels of tunable porosity, compact dried films. Suggested or already current applications of these systems are in the field of electronics, biomedical, textile, and printing technologies. This review reports on the recent and emerging trends in nanocellulose research concerning the behavior, design, and modification of its interface. This nanomaterial is obtained by a biological source and its behavior is dictated from the composition and structure of native cellulose. The understanding of interface phenomena and their manipulation are the main issues for the effective manufacture of emulsions, coatings and films. In reviewing the recent applications, emphasis is placed on the systems which require control of the order and dynamic of nanocellulose assembly to realize smart materials exploiting the rich and complex behavior of nanocellulose. Abstract : Nano‐scale structures obtained from cellulose show enhanced interfacial interactions responsible for colloidal properties, self‐assembly and fibril alignment. Here, the intriguing role of these interactions to set up protocols for emerging functional materials is reviewed. The perspective on the future way to improve the exploitation of the nanocellulose properties is reported.